Electrochemical Hydroxylation of C(3)–C(12)n-Alkanes by Recombinant Alkane Hydroxylase (AlkB) and Rubredoxin-2 (AlkG) from Pseudomonas putida GPo1 - Tsai, Yi-Fang (Sci Rep, 2017)
An unprecedented method for the efficient conversion of C(3)–C(12) linear alkanes to their corresponding primary alcohols mediated by the membrane-bound alkane hydroxylase (AlkB) from Pseudomonas putida GPo1 is demonstrated. The X-ray absorption spectroscopy (XAS) studies support that electrons can be transferred from the reduced AlkG (rubredoxin-2, the redox partner of AlkB) to AlkB in a two-phase manner. Based on this observation, an approach for the electrocatalytic conversion from alkanes to alcohols mediated by AlkB using an AlkG immobilized screen-printed carbon electrode (SPCE) is developed. The framework distortion of AlkB–AlkG adduct on SPCE surface might create promiscuity toward gaseous substrates. Hence, small alkanes including propane and n-butane can be accommodated in the hydrophobic pocket of AlkB for C–H bond activation. The proof of concept herein advances the development of artificial C–H bond activation catalysts.